Morphology is not always useful for diagnosis, and that’s ok: Species hypotheses should not be bound to a class of data. Reply to Brown and Gibbons (S Afr J Sci. 2022;118(9/10), Art. #12590) - Lawley, Jonathan W. (2022)
This paper serves as a reply to the Commentary by Brown and Gibbons (S Afr J Sci. 2022;118(9/10), Art. #12590) on our recently published paper on systematics of the moon jellyfish genus Aurelia (Lawley et al. PeerJ 2021;9, e11954)). We emphasise that we are not advocating for the routine use of molecular data alone in taxonomic diagnoses, rather that it is a valid approach in cases where, after detailed analyses, morphological features are shown to be unreliable.